Evaluation of Anticancer Activity of Ethanolic Extract of Strobilanthes ciliatus Leaves on HT–29 Cell Lines - Sebastian, Rani; Venkatachalam, Gomathi; D, Umamaheswari; M, Sakthi Abirami; BS, Venkateswarlu (Asian Journal of Biological and Life Sciences)
Aim: The present research is aimed to highlight the cytotoxic potential of Strobilanthes ciliatus on H T-29 cell lines. Materials and Methods: Extraction done with ethanol (SCLE) and Acetone (SCLA) by soxhlet method and anticancer by MTT assay. GCMS was used to analyze the phytochemicals of a particular plant, and MTT flow cytometry was used to assess cytotoxicity. Results: A total of 38 distinct compounds were found in this study’s analysis of the plant’s entire chemical profile, and three of those compounds were found in two different solvent extractions. LD was assessed using the MTT and flow cytometry methods, and the transmittance of the extraction-treated HT29 cell was determined using a plate reader at a wavelength of 570 nm. SCLE had the largest antiproliferative effect of the 2 investigated extractions, with an IC50 value of 33.62 g/mL, while the acetone extract had less impact. Conclusion: The results showed significant cytotoxic activity only on ethanol extraction, not by acetone extract, due to the concentration and diversity of compounds. The studies reveal that natural plant extract showed effective anticancer activities in vitro that can be further subjected to the development of a potential therapeutic anticancer agent.
Keywords: Anticancer; Anticancer activity; Cytotoxic.; cytotoxicity; HT-29 cell lines; MTT assay; Strobilanthes ciliatus IC50